2005
DOI: 10.1098/rspb.2004.3033
|View full text |Cite
|
Sign up to set email alerts
|

Limited genetic exchanges between populations of an insect pest living on uncultivated and related cultivated host plants

Abstract: Habitats in agroecosystems are ephemeral, and are characterized by frequent disturbances forcing pest species to successively colonize various hosts belonging either to the cultivated or to the uncultivated part of the agricultural landscape. The role of wild habitats as reservoirs or refuges for the aphid Sitobion avenae that colonize cultivated fields was assessed by investigating the genetic structure of populations collected on both cereal crops (wheat, barley and oat) and uncultivated hosts (Yorkshire fog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 61 publications
5
83
2
1
Order By: Relevance
“…Previous genetic studies on aphids have reported deviation from Hardy-Weinberg Equilibrium because of heterozygosity excess (Papura et al, 2003;Vialatte et al, 2005). Michel et al (2009a) observed similar levels of heterozygote excess with the soybean aphid, with more deviation present in early collected populations.…”
Section: Heterozygosity Excessmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous genetic studies on aphids have reported deviation from Hardy-Weinberg Equilibrium because of heterozygosity excess (Papura et al, 2003;Vialatte et al, 2005). Michel et al (2009a) observed similar levels of heterozygote excess with the soybean aphid, with more deviation present in early collected populations.…”
Section: Heterozygosity Excessmentioning
confidence: 68%
“…However, in some cases, especially with late populations, genotypic diversities were close or at maximum, that is, every individual was represented by a different clonal genotype. In these instances, we also included common population genetic statistics used in previous aphid genetic studies (Miller et al, 2003;Vialatte et al, 2005;Klueken et al, 2011), as data mirrored randomly admixed populations atypical of clonal reproduction. The probability of two individuals that share a MLG (that is, clones) resulting from a sexual reproduction event was calculated using P sex using GenClone (ArnaudHaond et al, 2007).…”
Section: Polymorphism and Genetic Diversity Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Native herbivore populations that shift onto agricultural crops can become genetically differentiated from populations that remain on the original host plant (Vialatte et al, 2005;Michel et al, 2010;Lavandero et al, 2011 Midamegbe et al, 2011;Barman et al, 2012;Bourguet et al, 2014). Because host shifts create new ecological opportunities for herbivores, population can diverge via ecological speciation in sympatry (Bush, 1969;Berlocher and Feder, 2002).…”
Section: Human-mediated Migration Of Crops Triggers Host Shiftsmentioning
confidence: 99%
“…Diversity is then a result of the interplay between genetic drift (including random mortality from environmental conditions or natural enemies), and selection through clonal amplification. Clonal amplification refers to the rapid increase in frequency in certain asexual clones through selection which is quite common in many aphid species during the asexual phase (Vorburger et al 2003;Vialette et al 2005), and likely occurs in soybean aphid . Currently, the use of soybean aphid resistant varieties is limited, therefore selective pressure and clonal amplification of specific virulent biotypes is not likely to occur.…”
Section: Population Biology Issues: the Distribution And Spread Of Bimentioning
confidence: 99%